Stopping The Scroll: Visual Triggers Of User Attention In Short-Video Advertising - Achmad Ridha (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The proliferation of short-video platforms has fundamentally altered advertising dynamics, compelling marketers to capture user attention within two to three seconds before the scroll moves on. While prior research has explored the experiential dimensions of attention and cognitive flow in TikTok advertising, no study has systematically identified and mechanistically explained the specific visual elements that arrest scrolling behavior and trigger initial attention, a gap that leaves the first causal link in the advertising effectiveness chain theoretically unaddressed. This study employs a qualitative explanatory approach to investigate which visual triggers are most effective in capturing user attention during short-video ad consumption and to explain the cognitive and perceptual mechanisms through which they operate. Drawing on stimulus-based semi-structured interviews with twelve active TikTok users in Makassar City, Indonesia, and guided by visual salience theory, the findings identify four dominant visual trigger categories: (1) dynamic motion and rapid transitions, (2) human facial expression and direct eye contact, (3) high-contrast color compositions, and (4) text overlay and caption placement. The study explains how each trigger operates through distinct perceptual pathways, activating bottom-up attentional capture before top-down cognitive processing can engage. These findings extend Ridha's (2024) phenomenological account of attention experience by moving beyond description to specify the visual mechanisms that initiate the attentional entry phase, a contribution that bridges visual salience theory with digital attention phenomenology in a non-Western short-video market. Practical implications are offered for digital advertisers designing scroll-stopping creative content in the Indonesian short-video market.